Water, energy, climate and livelihoods in India: strategies for smallholder prosperity with resilience - IWMI-Tata Water Policy Program (International Water Management Institute, 2025)
The IWMI-Tata Partners’ Meet 2024 was held from 18-20 September at the National Dairy Development Board Campus in Anand, India, brought together over 270 national and international participants to deliberate on critical issues at the intersection of water, energy, climate, agriculture, and rural livelihoods in India. Organized by the IWMI-Tata Water Policy Research Program, a co-equal partnership between IWMI and Tata Trusts, this flagship event featured curated plenary sessions and 18 technical sessions across four thematic tracks: Water-Energy-Livelihoods Nexus, Catalyzing Smallholder Prosperity, Water Governance and Risks and Emerging Themes. This document outlines the detailed three-day agenda of the Partners’ Meet, including a range of presentations, moderated panels, and field visits showcasing ITP's action research pilots in Dhundi and Saatordi in Gujarat. Plenary highlights included sessions on philanthropy’s role in water security, the media-practitioner-policy interface, and emerging challenges and solutions in the water sector.